1975
DOI: 10.1037/h0076736
|View full text |Cite
|
Sign up to set email alerts
|

Confounding of personality and social class characteristics in research on premature termination.

Abstract: The purpose of this study was to determine whether previous research in the area of premature termination had confounded personality with social class variables. It was hypothesized that while middle-and lower-class patients might differ on three personality characteristics previously shown to be related to premature termination, no differences on these personality characteristics would be found between patients who terminated and those who remained within any single social class. The Terminator-Remainer Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Stern et al (1975), who assessed 68 clients in an outpatient clinic, found no significant differences between those who continued in treatment and those who dropped out.…”
Section: Client Personality Characteristics Associated With Therapy Dmentioning
confidence: 94%
“…Stern et al (1975), who assessed 68 clients in an outpatient clinic, found no significant differences between those who continued in treatment and those who dropped out.…”
Section: Client Personality Characteristics Associated With Therapy Dmentioning
confidence: 94%
“…The recent article by Stern, Moore, and Gross (1975) pertaining to research on premature termination merits some comment. Even though these authors appear overly severe in their criticism of possible methodological shortcomings in some previously published studies, they apparently have overlooked some other important methodological problems that limit the generalizability of their own results and conclusions.…”
mentioning
confidence: 99%
“…Largely on the basis of a review of some older studies, Stern et al (1975) hypothesized "that the premature terminator's personality characteristics have been confounded with the personality characteristics of those patients who terminate most frequently, i.e., lower-class patients" (pp. 341-342).…”
mentioning
confidence: 99%
“…The comment by Garfield on the article by Stern, Moore, and Gross is responded to with specific reference to the adequacy of the measure of social class used in previous studies and to the interpretation of the data offered by Garfield. Several specific questions that Garfield asks about the Stern et al article are answered. Garfield (1977) points to some shortcomings in the study of Stern, Moore, and Gross (1975) to which we would like to respond. He points out that our study was overly critical of previous research in the area of premature termination.…”
Section: Ohio State Universitymentioning
confidence: 99%